STRATEGI MANAGEMEN LABA DARI LEVERAGE: BUKTI EMPIRIS PERUSAHAAN KELUARGA DAN NON-KELUARGA - RUSTAM HANAFI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2020)
This study aims to examine whether leverage is related to earnings management in family and non-family firms. This study also examines the role of family control in the relationship between leverage and earnings management. The sample selection of this study used a purposive sampling method so that the total sample that met was 264 firms. This study uses multiple regression analysis to determine the relationship between leverage and earnings management and the involvement of family-controlled and non-family firms. The results of this study show that leverage and family ownership have a significant negative effect on earnings management. Furthermore, the effect of leverage on earnings management is stronger for family-controlled firms than controlled by non-families. This result supports the view of entrechment, where family-controlled firms take over the wealth of minority shareholders for personal gain and hide by managing earnings, especially when the source of funding is through debt.